PENGOBATAN TRADISIONAL BALI EMPIRIS DALAM PERATURAN GUBERNUR BALI NOMOR 55 TAHUN 2019 TENTANG KESEHATAN TRADISIONAL BALI - Udiana, Gede Krisna; Bagiastra, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol 12 No 2 (2024)DO - 10.24843/KS.2024.v12.i02.p01, 2023)
This study aims to examine the effectiveness of Bali Governor Regulation Number 55 of 2019 on Balinese Traditional Health, which regulates the implementation of traditional Balinese medicine. This study uses a normative legal research method with a legislative and conceptual approach. The results of the study indicate the potential ineffectiveness of the regulation due to the inclusion of empirical definitions in Balinese Traditional Medicine practiced by Pengusadha/Balian and the exclusion of magical-spiritual values in the Ethical Criteria that must be accommodated in the establishment of the Pengusadha Code of Ethics regulated by this regulation. Both of these aspects contradict the beliefs of the Pengusadha concerning Sesananing Balian and the methods of traditional medical practice. This is in line with the theory of legal effectiveness, where societal and cultural factors must be accommodated in the formulation of regulations, especially in the legal objective as a tool for empowering society/social engineering. Keywords: Legal Effectiveness, Empirical Balinese Traditional Medicine, Sesananing Balian .